Improved knowledge, attitude, and practice during COVID-19 pandemic among Chinese in Mainland China compared to Malaysian - Li, Shucheng; Low, Bin Seng (International Journal of Public Health Science (IJPHS), 2025)
COVID-19 is currently inconspicuous yet to be eradicated. Since knowledge, attitude and practice (KAP) are important elements in containing the outbreak, it is worth ascertaining the KAP in preventing COVID-19. Present study compared the KAP of the respondents from the two countries China and Malaysia on COVID-19 outbreak. A cross-sectional questionnaire-based study was conducted. Descriptive statistics, Chi-square test, t-test and one-way ANOVA on the data were performed. A total of 390 respondents from Malaysia and 395 respondents from China were participated in the study. Results showed gender, education level, and age were associated with overall better knowledge (p<0.05) in China. In Malaysia, positive attitudes towards COVID-19 were more prevalent among degree holders and within the age range of 18 to 30 years. However, differences by gender, education level, age and monthly income between Chinese and Malaysian respondents on attitude were found significant (p<0.05). During the pandemic, the preventive practices were associated with education and age (p<0.05) for both Chinese and Malaysian respondents. In conclusion, Chinese respondents demonstrated better knowledge and more positive attitudes compared to Malaysians, highlighting the need for comprehensive educational programs in Malaysia to enhance public KAP regarding COVID-19 prevention, particularly among less educated and older populations.